(untitled) (The Review of Diabetic Studies, 2023)
BACKGROUND: The incidence of diabetes in the general population is increasing world-wide. The increase is attributed to the consumption of saturated fatty acids, obesity, lack of physical activity, genetic predisposition, and other factors, but knowledge about the reasons, biological mechanisms, and late complications is insufficient. It is therefore important to clarify the reasons more exactly through longterm clinical trials to stop the rise of diabetes and its complications. AIM: To evaluate the 10-year incidence of type 2 diabetes in apparently healthy Greek adults. METHODS: In 2001-2002, a random sample of 1514 men (18-87 years old) and 1528 women (18-89 years old) was selected to participate in the ATTICA study. During 2011-2012, the 10-year follow-up was performed. Patients diagnosed with diabetes at baseline (n = 210) and those lost at the 10-year follow-up (n = 1347) were excluded, yielding a final sample of 1485 participants. RESULTS: During the period of investigation, diabetes was diagnosed in 191 cases corresponding to a 12.9% incidence (95%CI: 10.4-15.4), with 13.4% (95%CI: 10.8-16) in men and 12.4% (95%CI: 10.1-14.7) in women. A relative increase was observed in the second half of the 10-year followup when age became significant. Multiple logistic regression analysis revealed that age (OR = 1.14, 95%CI: 1.09-1.19), abnormal waist-to-height ratio (OR = 3.27, 95%CI: 1.07-10.0), fasting blood glucose (OR per 1 mg/dl = 0.05, 95%CI: 1.02- 1.08), energy intake (OR per 500 kcal = 1.02, 95%CI: 1.01- 1.35), and family history of diabetes (OR = 2.8, 95%CI: 1.30- 6.03) were the most significant baseline predictors for diabetes, after adjusting for potential confounders. Waist-to-height ratio showed the best explanatory power of all anthropometric variables. Physical activity exerts an effect on risk factors. Being active was found to eliminate the aggravating effect of diabetes family history and fasting blood glucose. CONCLUSIONS: The findings confirm the escalating increase of type 2 diabetes incidence in Greece, which is in line with global trends. A lifestyle change in individuals at risk of developing diabetes towards healthier eating and increased physical activity would be an effective and inexpensive means of reducing diabetes.